Hubungan romantik dan remaja hamil luar nikah di pusat pemulihan - Salamatussaadah Abd. Ghadur,; Nor Ba’yah Abdul Kadir, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2009)
Studies on unwed pregnancy among adolescence are critical. Exploring of this issue would help in early preventing female adolescence to be involved in this social problem. The study aims to explore the meaning of romantic relationships and its relationships to social motives. This study was carried out from August to December 2009. A semi-structure interview was used to obtain the data. Of 15 potential informants, five of them have been selected to be interviewed. Other confidential documents were also used as triangulation process and validation as well. All interviews were recorded and transcribed. Thematic analysis was used to analyze the interview data. Results had shown that all informants defined romantic relationships in terms of sexually intimacy relationships whilst social motives were seen as experiencing love and to be loved, and happiness with adults